Beach-User Attitudes to Shark Bite Mitigation Strategies on Coastal Beaches; Sydney, Australia. Issue 3 (4th May 2017) - Gray, Georgia M. E.; Gray, Charles A.
ABSTRACT: Common strategies to protect swimmers from unprovoked shark bite incidents on coastal beaches are controversial. We surveyed beach users on two Sydney beaches to gauge their knowledge and attitudes to current and topical shark bite mitigation strategies. Most interviewees (>55%) were aware that shark nets were deployed on each beach, and gave relatively strong (>60%) support for their use. In contrast, beach users were overwhelming against (>80%) the general culling of sharks, and also opposed (>70%) the strategy of catching and killing sharks following a shark bite incident. There was little difference between genders in their attitudes to each strategy, but the oldest age category (51+) surveyed was generally most supportive of the lethal strategies. The results demonstrated the dichotomies in public attitudes to the different mitigation strategies, particularly passive versus active culling, and highlighted the need for greater public education for the development of socially acceptable solutions to shark hazards.